Optimal Dynamic Carbon Taxation in a Life-Cycle Model with Distortionary Fiscal Policy - Sebastian Rausch; Jan Abrell (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We quantitatively characterize optimal carbon, capital, and labor income taxes in an economy-climate integrated assessment model that features overlapping generations and distortionary fiscal policy. First, we show that the optimal carbon tax significantly differs from the Pigouvian carbon levy in a first-best setting with overlapping generations in which fully rational households optimize over finite lifetimes. The key driving force behind this result is the life-cycle structure of the our model, in conjunction with endogenously chosen labor supply. We also show that the assumed labor supply elasticity is important for the size of deviation of the optimal carbon tax from the Pigouvian tax, but not the existence of the deviation from Pigouvian pricing. Second, interacting life-cycle household behavior with distortionary fiscal policy is shown to further drive a wedge between the second-best optimal carbon tax and a Pigouvian carbon levy.
Keywords: E13; H21; H24; 330